THE MORAL CONCEPT OF TASAWUF IN THE PROCESS OF ISLAMIC EDUCATION - Giantomi Muhammad; Nurwadjah Ahmad Eq; Andewi Suhartini (TA'DIB: JURNAL PENDIDIKAN ISLAM, 2021)
Sufism teachings are increasingly needed in the current era of globalization as an effort to minimize the ugliness as well as the gap in human attitudes towards oneself, fellow humans, and also Allah SWT. The practice of Sufism which is exemplified by the Sufis in general provides a side of religious values that results in a noble moral behavior. Noble morals give hope for the formation of an advanced civilization and do not ignore the divine values that always exist in human life. The purpose of this research is the formation of a scientific concept regarding the character of Sufism that is sustainable in the process of Islamic education. The method in this research uses the method of literature study, analysis of reading content, and descriptive analysis of various related sources. The results of the study found a concept that the character of Sufism produced ihsan attitudes that needed to be internalized in the process of Islamic education as an effort to foster noble moral behavior, both towards Allah, himself, fellow humans, and other living creatures in the universe.